THE METHOD OF RELIABILITY ESTIMATION OF THE AUTOMATED CONTROL SYSTEM FUNCTIONING OF TRACTION POWER SUPPLY OF ELECTRIC TRANSPORT - Matusevych, O. O. (Science and Transport Progress, 2009)
The author proposed the examination method for estimating the reliability of functioning a system of automated control of traction electric supply systems for electric transport in order to organize the work with specialists-experts and to treat with experts’ opinions. This method enables us to make a decision about planning and taking the examination and forming the group of experts to conduct the results analysis and prepare the conclusions for people who make the decision on improving the reliability of a system of automated control of traction electric supply systems.